2019
DOI: 10.2147/ott.s190093
|View full text |Cite
|
Sign up to set email alerts
|

<p>Leptin rs7799039 (G2548A) polymorphism is associated with cancer risk: a meta-analysis involving 25,799 subjects</p>

Abstract: Background: Leptin (LEP) is a human analogous form of the mouse obese gene and plays a critical role in energy expenditure as well as the progression of carcinogenesis. Many studies exploring the relationship between the LEP rs7799039 (G2548A) polymorphism and cancer risk have observed controversial results. To extensively evaluate this potential association, we conducted this meta-analysis. Methods: All eligible studies published up to August 2018 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Of the PON1 polymorphisms, PON1 rs662 and rs854560 are most widely studied for their association with susceptibility to different cancers (Seow et al, 2016). Moreover, human LEP gene plays a critical role in energy expenditure as well as the progression of carcinogenesis (Tang et al, 2019). It is also reported that LEP may affect angiogenesis, inflammation, thrombosis, and tumor growth, invasion, and metastasis (Tang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the PON1 polymorphisms, PON1 rs662 and rs854560 are most widely studied for their association with susceptibility to different cancers (Seow et al, 2016). Moreover, human LEP gene plays a critical role in energy expenditure as well as the progression of carcinogenesis (Tang et al, 2019). It is also reported that LEP may affect angiogenesis, inflammation, thrombosis, and tumor growth, invasion, and metastasis (Tang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, human LEP gene plays a critical role in energy expenditure as well as the progression of carcinogenesis (Tang et al, 2019). It is also reported that LEP may affect angiogenesis, inflammation, thrombosis, and tumor growth, invasion, and metastasis (Tang et al, 2019). It is revealed that the LEP signal may be transmitted through several signaling pathways such as JAK/STAT, MAPK, PI3K, Wnt/β-catenin, and ERK (Kavitha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When significant heterogeneity ( I 2 >50% or P <0.10) was found, the random-effects model (the DerSimonian–Laird method) was used [ 26 , 27 ]. And when it is out of heterogeneity, fixed-effects model was implemented (the Mantel–Haenszel method) [ 28 , 29 ]. Four major genetic models were harnessed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Encouraged by the results of our earlier study on − 2548A/G and taking into consideration the role the abovementioned SNP plays in cancer risk [6][7][8], we decided to go further and investigate and elucidate, if polymorphic variants of LEP-R may also alter the hazard of endometrial cancer. In this study we have aimed to determine the influence of SNP rs1137101 A>G polymorphism (p.Gln223Arg) of LEP-R on its allele-specific expression in women with endometrial cancer with further analysis of its interrelation with obesity.…”
Section: Introductionmentioning
confidence: 99%